2019
DOI: 10.1259/dmfr.20190209
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CBCT on treatment decision related to surgical removal of impacted maxillary third molars: does CBCT change the surgical approach?

Abstract: Objectives: To assess factors influencing treatment decision for maxillary third molars referred for cone beam CT (CBCT). Parameters influencing the decision to treat and to remove either the maxillary second molar or third molar were pursued. Methods: 111 impacted maxillary third molars, clinically examined including a panoramic image, in 86 patients (mean age 26 years, range 15–55) were referred for CBCT on suspicion of pathology/root resorption in the second molar, based on information in the panoramic imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…In previous studies, the authors compared CBCT and OPG on many different aspects such as: surgical technique of maxillary and mandibular third molar, classifying of lower third molar, upper molar root protrusion into maxillary sinus, relation of impacted mandibular third molars to the inferior alveolar nerve, presurgical evaluation of bony implant sites, impacted maxillary canines, and anatomical characteristics and visibility of mental foramen and accessory mental foramen (Ghaeminia et al,2009;Aravindaksha et al, 2015;Lorenzo et al, 2015;Pico et al, ;Araujo et al, 2019;Hermann et al, 2019;Brasil et al, 2019;Themkumkwun et al, 2019;Nirmalendu et al, 2019;Fortes et al, 2019). None of the prior studies compared CBCT and OPG films taken after the marsupialization of odontogenic cysts in terms of evaluating whether the odontogenic cyst volume allows enucleation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, the authors compared CBCT and OPG on many different aspects such as: surgical technique of maxillary and mandibular third molar, classifying of lower third molar, upper molar root protrusion into maxillary sinus, relation of impacted mandibular third molars to the inferior alveolar nerve, presurgical evaluation of bony implant sites, impacted maxillary canines, and anatomical characteristics and visibility of mental foramen and accessory mental foramen (Ghaeminia et al,2009;Aravindaksha et al, 2015;Lorenzo et al, 2015;Pico et al, ;Araujo et al, 2019;Hermann et al, 2019;Brasil et al, 2019;Themkumkwun et al, 2019;Nirmalendu et al, 2019;Fortes et al, 2019). None of the prior studies compared CBCT and OPG films taken after the marsupialization of odontogenic cysts in terms of evaluating whether the odontogenic cyst volume allows enucleation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Ghaeminia et al (2009) reported that CBCT images before mandibular third molar surgery had a dramatic effect in surgical planning in the direction of tooth removal regarding buccolingual relationship between tooth and mandibular canal. Also, Hermann et al (2019) determined that CBCT images changed the treatment plan regarding external root resorption compared to panoramic images. According to Hermann el al.…”
Section: Discussionmentioning
confidence: 99%
“…47 CBCT of impacted maxillary canines should be evaluated both by multiplanar reconstruction (MPR) and by -curved‖ reconstructions and not just by one. 48 CBCT has now been extensively applied to a wide range of lesions arising within or affecting the jaw bones. 21,49,50 Large field-of-view cone-beam computed tomography CBCT imparts a larger radiation dose to the patient than conventional radiography, including panoramic radiographs.…”
Section: Focused or Small Field-of-view Cone Beam Computed Tomographymentioning
confidence: 99%
“…Furthermore, CBCT was invaluable in the discernment of the more complicated root pattern of maxillary molars not only for endodontic purposes, 40 but also presurgical planning that contemplates extraction. 48 Observation of severe external root resorption of the maxillary second molar by the impacted third molar often resulted in the removal of the former and retention of the latter. 47 CBCT of impacted maxillary canines should be evaluated both by multiplanar reconstruction (MPR) and by “curved” reconstructions and not just by one.…”
Section: How Covid-19 May Cause Changes In the Prescription Of Radiogmentioning
confidence: 99%
See 1 more Smart Citation